2022
DOI: 10.1002/ijc.34247
|View full text |Cite
|
Sign up to set email alerts
|

The presence of vessels encapsulating tumor clusters is associated with an immunosuppressive tumor microenvironment in hepatocellular carcinoma

Abstract: Recently, a distinct vascular pattern in hepatocellular carcinoma (HCC) called vessels encapsulating tumor‐forming clusters (VETC) has received attention because of its association with poor prognosis. However, little is known about the mechanism by which VETC promotes an aggressive phenotype at the molecular level. In our study, the association between differences in stepwise signal intensity in the HB phase and molecular subtypes and somatic mutations associated with the immune microenvironment were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…11 In the present study, the Previous studies have revealed that VETC-positive HCC has fewer tumor-infiltrating CD3-positive cells than VETC-negative HCC, 29 and their transcriptional analysis shows molecular characteristics indicative of lower immune activation. 16 Likewise, the majority of VETC-positive HCC cases are categorized into the immune-low/angiogenic immunovascular subtype. 17 In the present study, we observed that the number of CD8-positive cells was significantly lower in VETC-positive HCC than that in VETCnegative HCC, which is consistent with the previous studies, 16,17 suggesting that VETC-positive HCC cells are more likely to escape from immune attacks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 In the present study, the Previous studies have revealed that VETC-positive HCC has fewer tumor-infiltrating CD3-positive cells than VETC-negative HCC, 29 and their transcriptional analysis shows molecular characteristics indicative of lower immune activation. 16 Likewise, the majority of VETC-positive HCC cases are categorized into the immune-low/angiogenic immunovascular subtype. 17 In the present study, we observed that the number of CD8-positive cells was significantly lower in VETC-positive HCC than that in VETCnegative HCC, which is consistent with the previous studies, 16,17 suggesting that VETC-positive HCC cells are more likely to escape from immune attacks.…”
Section: Discussionmentioning
confidence: 99%
“…16 Likewise, the majority of VETC-positive HCC cases are categorized into the immune-low/angiogenic immunovascular subtype. 17 In the present study, we observed that the number of CD8-positive cells was significantly lower in VETC-positive HCC than that in VETCnegative HCC, which is consistent with the previous studies, 16,17 suggesting that VETC-positive HCC cells are more likely to escape from immune attacks. The reduction in tumor-infiltrating CD8positive cells is indicative of an adverse prognostic factor, [30][31][32] which potentially contributes to the poor prognosis associated Interestingly, we found that background liver cirrhosis was negatively associated with the presence of VETC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VETC and MTM patterns are primarily represented by IL/AG subtypes. Zhang et al [33] used RNAseq data to analyze molecular patterns in the VETC+ and VETC− groups. This analysis detected an increased enrichment of mRNAs associated with an efficient immune response in the VETC+ group.…”
Section: Analysis Of Immunitymentioning
confidence: 99%
“…This analysis detected an increased enrichment of mRNAs associated with an efficient immune response in the VETC+ group. Thus, it appears that tumors evade the immune system because of a molecular feature that inhibits normal responses of the immune system to tumor cells [33]. These results suggest that the immunosuppressive microenvironment of HCC may affect the formation of MTM and VETC patterns.…”
Section: Analysis Of Immunitymentioning
confidence: 99%